Changes in Chinese's political involvement in Malaysia - Lee, Yok Fee (Universiti Putra Malaysia Press, 2010)
Malaysian Chinese is the second largest group in the country’s population and has been actively involved in politics since their mass immigration during the middle of the 19th century. The main objective of this article is to examine the political involvement of the Chinese, their voting behaviour, bureaucratic participation and reaction to Malay dominance in the country in different periods, i.e. pre- and post-1970, and post-2008 General Elections. This writing is greatly contingent upon a content analysis on secondary data collected from reports, journal articles, book chapters, and newspaper articles. In short, Chinese’s involvement and reaction in politics in Malaysia significantly depend on the discourse of Malay dominance. Malaysian Chinese’s political participation in the period from 1970 to 1990 indicated both continuity and change. Chinese electorate’s voting patterns seem to demonstrate a swing to the opposition candidates, while the parties in the Barisan Nasional government continue to enjoy the confidence of the Malay communities as well as the elites. Meanwhile, the so-called politic tsunami on 8 March 2008 has opened a new phase in the Malaysian political development. The nature of politics is said to have shifted from communal-based politic to multiethnic-based.